K.I. Rovinskiy in the History of Tax Accounting in Russia - V. Ya. Sokolov (Учёт. Анализ. Аудит, 2024)
The paper studies the life and work of the founder of the tax accounting history, Konstantin I. Rovinskiy.The relevance of this publication is determined by the insufficient study of the history of tax accounting in Russia.It uses the prosopographical method and the method of archival research.The author’s goal is to emphasize Rovinskiy’s contribution to financial science. This involves justifying indirect taxation compared to direct taxation, determining the most effective tax administration structure, establishing procedures for collecting excise tax on alcohol, auditing financial activities, and encouraging adherence to ethical standards among financial workers. His major work, “Tax Inspectorate in Russia”, is one of the most cited publications on the history of taxation. Rovinskiy’s contribution to the social movement is important. He shared the political ideas of the zemtsovs, and wrote his articles in newspapers under the pseudonym Zemets. Despite his liberal views, participation in a club of political figures, in a conference on introducing a self-state in Russia. Rovinskiy lectured on religious issues, in which he had substantiated the need for separation of church and state. Throughout his career in the civil service, Rovinskiy held various positions, including the head of the department of tax collection of the Ministry of Finance, as well as management roles in the Courland treasury chamber in Mitava and Orel. He eventually rose to the rank of actual state councilor. The revolution changed his fate and interrupted his civil service, but opened up spiritual service for him. His high spiritual qualities helped him survive many arrests and exile. The manuscript department of the Russian State Library currently holds Rovinskiy’s works, but regrettably, they have yet to publish them. They are valuable not only as a historical document but also as a wonderful literary composition.